2010
DOI: 10.1038/labinvest.2010.94
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells and their role in atherogenesis

Abstract: Dendritic cells (DCs) are the most potent professional antigen-presenting cells with the unique ability of primary immune response initiation. DCs originate from bone marrow progenitors, which circulate in the peripheral blood and subsequently penetrate peripheral tissues, where they give rise to immature DCs. In peripheral tissues, DCs continuously monitor the microenvironment and, when the cells encounter 'danger' signals, DCs undergo differentiation and maturation. Maturing DCs usually migrate to lymphatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 160 publications
(503 reference statements)
5
79
0
2
Order By: Relevance
“…57 Ultrastructural studies of human atherosclerotic lesions demonstrated that CD68 is mostly located in lysosomes (Figure 3). 58,59 In contrast to macrophages, 59 CD68 is not expressed by dendritic cells (DCs) 14,60 and this helps to immunohistochemically distinguish these two cell types, both of which have antigenpresenting capabilities. Several studies have shown significant upregulation of CD68 expression in macrophages in response to inflammatory stimuli such as exposure to oxLDL 12,49,50 and chronic stimulation with bacterial lipopolysaccharide (LPS) or inflammatory cytokine interferon-γ (IFN-γ).…”
Section: Cd68: a Role In Inflammation And Immunitymentioning
confidence: 99%
“…57 Ultrastructural studies of human atherosclerotic lesions demonstrated that CD68 is mostly located in lysosomes (Figure 3). 58,59 In contrast to macrophages, 59 CD68 is not expressed by dendritic cells (DCs) 14,60 and this helps to immunohistochemically distinguish these two cell types, both of which have antigenpresenting capabilities. Several studies have shown significant upregulation of CD68 expression in macrophages in response to inflammatory stimuli such as exposure to oxLDL 12,49,50 and chronic stimulation with bacterial lipopolysaccharide (LPS) or inflammatory cytokine interferon-γ (IFN-γ).…”
Section: Cd68: a Role In Inflammation And Immunitymentioning
confidence: 99%
“…For example, it has been demonstrated in several studies that T cells are one of the first cells to invade the arterial intima, later followed by macrophages, DCs, and SMCs in predisposed sites (Xu et al 1990;Kleindienst et al 1993;Millonig et al 2002). However, it has been shown that preexisting vascularassociated dendritic cells (VADCs) are presented in the tertiary lymphoid structures in the aortic adventitia at predisposed sites, even before the invasion of T cells (Bobryshev andLord 1996, 1998;Waltner-Romen et al 1998;Millonig et al 2001a, b;Liu et al 2008;Bobryshev 2010;Cybulsky and JongstraBilen 2010). These DCs can function as antigen-presenting cells (APCs) and thereby capture potentially harmful exogenous or autoantigens and present these to T cells and macrophages.…”
Section: Hsp60 In Human Atherosclerosismentioning
confidence: 99%
“…Inflammatory M1 macrophages are thought to play a role in the progression and instability of atherosclerotic plaques [67], while M2 macrophages are thought to be anti-inflammatory and atheroprotective [68] (Figure 1). However M2 macrophages take up lipids more readily and become foam cells more easily [69] than M1 macrophages.…”
Section: Macrophage Infiltration and Pathology In The Heart During Simentioning
confidence: 99%